2022
DOI: 10.3389/fimmu.2022.779585
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis in Rheumatoid Arthritis: A Potential Therapeutic Strategy

Abstract: Ferroptosis is one of the newly discovered forms of cell-regulated death characterized by iron-dependent lipid peroxidation. Extensive research has focused on the roles of ferroptosis in tumors, blood diseases, and neurological diseases. Some recent findings have indicated that ferroptosis may also be related to the occurrence and development of inflammatory arthritis. Ferroptosis may be a potential therapeutic target, and few studies in vitro and animal models have shown implications in the pathogenesis of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 76 publications
0
42
0
1
Order By: Relevance
“…Iron is found in the synovial membrane of lesions and is known to be a catalyst for H 2 O 2 production of • OH via the Fenton reaction [ 38 ]. The degenerative process of RA development may be aided by lipid peroxidation-related ferroptosis [ 39 , 40 ]. Notably, sulfasalazine indirectly increases ferric iron levels, triggering the Fenton reaction, which produces excess lipid ROS and causes ferroptosis [ 41 ].…”
Section: The Production Of Ros In Synovitismentioning
confidence: 99%
“…Iron is found in the synovial membrane of lesions and is known to be a catalyst for H 2 O 2 production of • OH via the Fenton reaction [ 38 ]. The degenerative process of RA development may be aided by lipid peroxidation-related ferroptosis [ 39 , 40 ]. Notably, sulfasalazine indirectly increases ferric iron levels, triggering the Fenton reaction, which produces excess lipid ROS and causes ferroptosis [ 41 ].…”
Section: The Production Of Ros In Synovitismentioning
confidence: 99%
“…Interestingly, recent studies in patients with rheumatoid arthritis (RA) showed that prolonged treatment with CQ and HCQ decreased the risk of Parkinson’s disease (PD), indicating anti-neurodegenerative properties ( Paakinaho et al, 2022 ). Indeed, as CQ and HCQ inhibit CatB, a protein implicated in the pathogenesis of both RA and PD, it is likely that these drugs inhibit CatB ( Hashimoto et al, 2001 ; Tsujimura et al, 2015 ; Mahoney-Sánchez et al, 2021 ; Zhao et al, 2022 ).…”
Section: Chloroquine and Hydroxychloroquinementioning
confidence: 99%
“…However, iron overload is a necessary condition to induce ferroptosis in cells, and ferroptosis plays an important role in the pathogenesis of inflammatory joint diseases such as rheumatoid arthritis. 15 It is a great pity that this study has not yet provided additional validation of the results by iron chelating therapy. In the next studies, we will investigate through more experiments whether iron overload or ferroptosis in cells is involved in the pathogenesis of AGA and how to induce or aggravate joint inflammation.…”
mentioning
confidence: 90%